A novel heterozygous SIX1 missense mutation resulted in non-syndromic unilateral hearing loss - Li, Ang; Liu, Siwen; Zhang, Peng; Hu, Xintong; Li, Guiying; Gu, Weiyue; Jiang, Yanfang (Frontiers in Genetics, 2022)
Familial non-syndromic unilateral hearing loss (NS-UHL) is rare and its genetic etiology has not been clearly elucidated. This study aimed to identify the genetic cause of NS-UHL in a three-generation Chinese family. Detailed medical history consultation and clinical examination were conducted. Further, whole-exome sequencing (WES) was performed to identify the genetic etiology of the proband, and the variant was verified by Sanger sequencing. A novel missense mutation, c.533G>C (p.Arg178Thr), in the SIX homeobox 1 gene (SIX1) was identified in four patients and co-segregated with NS-UHL in a three-generation Chinese family as a dominant trait. Using bioinformatics analyses, we show that this novel mutation is pathogenic and affects the structure of SIX1 protein. These data suggest that mutations in SIX1 gene are associated with NS-UHL. Our study added the NS-UHL phenotype associated with SIX1, and thereby improving the genetic counseling provided to individuals with SIX1 mutations.